Pengaruh Praktik Kerja Industri, Motivasi Kerja dan Kompetensi Siswa Terhadap Kesiapan Kerja - Sari, Reny Eka; Wahyono, Wahyono (Universitas Negeri Semarang, 2020)
The purpose of this research is to determine the impact of job training, job motivation and students competencies on the work readiness of office administration studenst XIth Grade of Vocational School in Pemalang. The population in this research was all of Office Administration Student XIth Grade of Vocational High School in Pemalang, there were 298 students. The sampling technique was proportional stratified random sampling which was calculated using Slovin formula with a total sample of 171 students. Data were collected using questionnaires and documentation and analyzed by descriptive analysis and multiple regression analysis. The results of the calculation data obtained by the multiple regression equation Y = 3,925 + 0,173x1 + 0,359x2 + 0,345x3 + e. The result of this study showed that job training, job motivation and students competenciesindirect affect to work readiness of office administration students XIth Grade of Vocational School in Pemalang.